Kinetics of chlorophyll pigment degradation of pakcoy (Brassica rappa L.) juice during thermal process - Wiyono, Andi Eko; Rusdianto, Andrew Setiawan; Ulya, Asyafa’atul; Setyawati, Putu Dewi Ratih (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Pakcoy (Brassica rappa L.) is a horticultural commodity with great potential that requires further processing to preserve quality and extend their shelf life. One of the commonly used advanced processing techniques is the pasteurization method, which uses a thermal process. The thermal process is known to cause quality degradation in pakcoy juice, especially its chlorophyll content. This study is to determine chlorophyll pigment degradation kinetics in pakcoyjuice during the thermal process. The kinetics of chlorophyll degradation followed first-order reactions, with an activation energy of 38.24 kJ/mol. The ? value ranged from 114.943 to 384.615 minutes, the ? value was 60.61°C, and the reaction rate constant (?) increased with increasing temperature. The results of this study emphasized the importance of controlling the temperature and duration of the thermal process to maintain the quality of chlorophyll pigments in pakcoy juice.